The clinical implications and biological relevance of neurofilament expression in gastroenteropancreatic neuroendocrine neoplasms - Schimmack, Simon; Schmitz-Winnenthal, Friedrich Hubertus; Fischer, Lars; Büchler, Markus W. (Cancer, 2012)
Background: Although gastroenteropancreatic neuroendocrine neoplasms (GEP-NENs) exhibit widely divergent behavior, limited biological information, apart from Ki67, is available to characterize malignancy. Identification of alternative biomarkers is therefore a key unmet need. Given the role of Internexin-alpha (INA)in neuronal development, we assessed its function in neuroendocrine cell systems and the clinical implications of its expression as a GEP-NEN biomarker. Methods: Functional assays were undertaken to investigate the mechanistic role of INA in the pancreatic BON cell-line. Expression levels of INA were investigated in 50 pancreatic NENs (43 primaries,7 metastases), 43 small intestinal NENs (25 primaries, 18 metastases), normal pancreas (10)and SI-mucosa (16), normal EC cells (9), mouse xenografts (4) and NEN cell lines (6)by qPCR, western blot and immunostaining. Results: In BON cells, decreased INA mRNA and protein were associated with inhibition of both proliferation and MAPK signaling. INA was not expressed in normal neuroendocrine cells but was over-expressed (2 to 42-fold) in NEN cell lines and murine xenografts. In pNENs, INA was over-expressed compared to pancreatic adenocarcinomas and normal pancreas (p=0.0001, 27-fold; p=0.02, 9-fold). INA transcripts positively correlated with Ki67 (r=0.5, p<0.0001) and CgA (r=0.59, p<0.0001). INA distinguished primaries and metastases (p=0.02). Expression was correlated with tumor size, infiltration and grade (p<0.05). Conclusion: INA is a novel NEN biomarker whose expression associated with MAPK signaling and proliferation. In clinical samples, elevated INA correlated with Ki67and identified malignancy. INA may provide additional biological information relevant to delineation of both pNEN tumor phenotypes and clinical behavior.